Female athletes' knowledge of biopsychosocial puberty-related topics in sports. What is missing? - Radovan, Felicia; Solstad, Bård Erlend; Kjær, Jørgen Bagger; Melin, Anna; Ausland, Ådne; Bjärsholm, Daniel; Ivarsson, Andreas; Torstveit, Monica Klungland; Laxdal, Aron; Ryman Augustsson, Sofia; Linner, Susanne (Frontiers in Sports and Active Living, 2025)
IntroductionPuberty has been identified as one of the main contributing factors for girls dropping out of sports during adolescence. Knowledge and social support can, however, help athletes navigate the biopsychosocial (BPS) puberty-related changes associated with this period. Yet, research on female athletes' knowledge about BPS puberty-related topics is lacking. Therefore, this cross-sectional study aimed to examine female athletes' perceived knowledge and knowledge needs of BPS puberty-related topics during adolescence, explore interconnections across BPS domains, and investigate differences between athletes in team and individual sports.MethodA total of 1,323 Swedish and Norwegian female athletes (M age 18.7 ± 2.3 years, range 16–24) from ten sport disciplines [n = 657 (49.7%) team sport athletes; n = 656 (49.6%) individual sport athletes] completed an online survey in 2024 on perceived knowledge and knowledge needs regarding BPS puberty-related topics during adolescence.ResultsFindings revealed low perceived knowledge and high knowledge needs among female athletes. A Mann–Whitney U test revealed higher perceived knowledge among team sport athletes regarding individual differences, social cohesion, social comparison, acceptance within the group, and recovery, compared to individual sport athletes. Additionally, team sport athletes reported higher knowledge needs regarding social comparisons, sports nutrition and recovery, while individual sport athletes reported higher knowledge needs regarding changes in sex hormones, individual differences, and changes in body composition. A network analysis identified clusters of biological, psychosocial, and behavioral topics in perceived knowledge and knowledge needs, indicating that knowledge is concentrated within domains.DiscussionThe findings highlight gaps in knowledge among female athletes regarding BPS puberty-related topics across various sporting contexts. The results also underscore the urgent need for holistic and interdisciplinary educational programs addressing these knowledge gaps in the sporting context of female athletes.